GAMBARAN STRATEGI PENJUALAN BINGKAI KACAMATA UNTUK MENINGKATKAN DAYA SAING DI OPTIK OCTA 12 - Budiana, Wahyu; Nugraha, Opep Cahya (Jurnal Mata Optik, 2026)
Sales strategy  are one way to win a sustainable competitive advantage for companies that produce goods or services. Sales strategy can be seen as one of the basics used in planning a company as a whole. Viewed from the breadth of the problems that exist within the company, it is necessary to have a comprehensive plan as a guide for the company's segments in carrying out their activities, another reason that shows the importance of sales techniques is the increasingly fierce competition in companies in general. sales to increase competitiveness, and to find out how effective the implementation of sales techniques has been. This research was conducted at Optik Octa 12 Citayam Depok. Data collection techniques with documentation, interviews and  observations, the type of research is descriptive research. The results of the analysis of the effectiveness of sales techniques show an increase in total sales from year to year and serve as a reference for the effectiveness of marketing strategies in competition between optical businesses